2015
DOI: 10.1111/eth.12443
|View full text |Cite
|
Sign up to set email alerts
|

Male Success in Intrasexual Contests Extends to the Level of Sperm Competition in a Species of Dung Roller Beetle

Abstract: Contests between males fighting over limited resources often determine the reproductive success of the contestants. It is possible that the outcomes of such contests are affected by traits that also contribute to the likelihood of males achieving paternity when sperm from multiple males compete to fertilize the ova of a single female; however, this relationship has been poorly characterized. In dung and carrion roller beetles, contests among males for the possession of a food balla vital resource for nestingar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Fights among male roller beetles for the ownership of a food ball during rolling and nesting have been widely documented [ 26 – 27 , 33 34 ], showing that ownership of the food ball, together with size (RHP) asymmetries, predict fight outcome. Our results show that food ball female owners of C .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fights among male roller beetles for the ownership of a food ball during rolling and nesting have been widely documented [ 26 – 27 , 33 34 ], showing that ownership of the food ball, together with size (RHP) asymmetries, predict fight outcome. Our results show that food ball female owners of C .…”
Section: Discussionmentioning
confidence: 99%
“…Males fight for food which allows the winner to obtain a mate. In Canthon cyanellus cyanellus , a carrion roller beetle, asymmetries in ownership and RHP during male-male contests influence the ability of the contestant to defend or gain food resources for reproduction [ 32 – 34 ]. Furthermore, the reproductive status of both contenders is also related to the chance of winning: previously mated owners have a higher probability of winning than virgin owners.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that the combat outcome can significantly affect the reproductive success of both combatants. Winning males increase their acquired paternity under conditions of sperm competition compared to loser males in previous combats (Chamorro-Florescano and Favila, 2016;Chamorro-Florescano et al, 2017).…”
Section: Sperm Competition and Female Selectionmentioning
confidence: 99%
“…However, the female may also perform sperm choice of specific phenotypes by shedding sperm and biasing sperm utilization by muscle contractions, among other possible mechanisms (Eberhard, 1996). These mechanisms have not been explored, but it has been reported that C. cyanellus females may benefit certain males having reproductive experience and a successful combat outcome (Chamorro-Florescano and Favila, 2016;Chamorro-Florescano et al, 2017).…”
Section: Sperm Competition and Female Selectionmentioning
confidence: 99%